Talking and Acting A Pandemic Ethnography of COVID-19 in Montmartre - Black, Alexis (Anthropologica, 2023)
Informed by eighteen months of ethnographic fieldwork in Montmartre, one of the last village-like neighbourhoods in Paris, in this paper, I analyze how people in this community talked through and acted out the COVID-19 pandemic. Using theoretical frameworks from linguistic, cognitive and medical anthropology, I examine “small stories” (Georgakopoulou 2007) about COVID-19, in particular, the analogical and conceptual aspects of this talk. How do people construct understandings of crisis as it evolves? What does this process look like when talk becomes action and reaction and what does it say about the future? This paper explores how people employed analogy, cultural scripts and other linguistic wor(l)d-building tools in their talk about their experiences and comprehensions of COVID-19. Following the arguments of Ochs (2012), I propose that talking about COVID-19 is itself an experience of the virus, an experience that informs people’s understandings of their present circumstances and future possibilities.